THE EFFECT OF NON PERFORMING LOANS TO CASH RATIO ON BANK BPR KERTARAHARJA - Winna Roswinna; Feby Febrian; Granit Agustina; Maria Lusiana Yulianti; Anne Lasminingrat (Dinasti International Journal of Education Management And Social Science, 2020)
In this study there are two variables, namely variable X (NPL) and Y variable (CR). This research was conducted to determine the effect of NPL on CR Bank BPR Kertaraharja. The method used in this research is descriptive analysis method to identify how the influence of NPL and how big CR is at Kertaraharja Rural Bank. While the verification of the analysis to identify the problem is how much influence the NPL has on the CR of BPR Kertraharja bank. This research was conducted at the BPR Kertaraharja Bank office. This research was conducted using a sample based on Purpose Sampling. The hypothesis of this study is that NPL has an effect on CR at the BPR Kertaraharja Bank. To measure the effect of these variables using Simple Linear Regression with the help of the application software system SPSS 21.0. Based on the results of data analysis using statistical methods, it was concluded that there was a significant influence between NPLs on CR banks, this was based on regression analysis with the equation Y = 24,985 - 1,312X. In correlation there is a fairly strong relationship between NPL and bank CR with a value of 0.680. Then the coefficient of determination (KD) is obtained that the NPL affects the CR with a value of 46.3%. Test the hypothesis of this study in which the t count of 4,147 is greater than the t table value of 2012. Then H1 is accepted and H0 is rejected, which means that NPL has a strong influence on bank CR.